Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1017/s0954579499002369
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral disinhibition and the development of substance-use disorders: Findings from the Minnesota Twin Family Study

Abstract: One variant of substance-use disorder is characterized by behavioral disinhibition. In this report, we martial evidence for a model for the development of this variant. We hypothesize that genetic liability for this variant is reflected in a spectrum of risk indicators linked to the inability or unwillingness to inhibit behavioral impulses. Included in this spectrum are personality traits suggesting low constraint, and externalizing psychopathology, including conduct, oppositional defiant, and attention-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
650
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 558 publications
(677 citation statements)
references
References 24 publications
(13 reference statements)
24
650
1
Order By: Relevance
“…Participating families were broadly representative of the Minnesota population at the time the twins were born; approximately 98% are Caucasian. Further information regarding the design, recruitment procedures, participation rates, and zygosity determination procedures of the MTFS can be obtained elsewhere (Iacono, Carlson, Taylor, Elkins, & McGue, 1999).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Participating families were broadly representative of the Minnesota population at the time the twins were born; approximately 98% are Caucasian. Further information regarding the design, recruitment procedures, participation rates, and zygosity determination procedures of the MTFS can be obtained elsewhere (Iacono, Carlson, Taylor, Elkins, & McGue, 1999).…”
Section: Methods Participantsmentioning
confidence: 99%
“…The perspective here is that heightened reactivity of this system is associated with difficulties in processing of emotional cues in dynamic situational contexts, leading to affective dysregulation expressed as distress, anger and reactive aggression (Blair, 2013;Blair et al, 2014). Elsewhere, Iacono et al (1999) demonstrated heightened physiological (electrodermal) reactivity to aversive noise blasts among highdisinhibited participants in a condition in which the blasts were signaled and thus predictable. 2 Whereas low-disinhibited participants were able to use the predictive signal to down-regulate their responses to the succeeding noise blasts, high-disinhibited subjects were not-reacting at increased levels to the blasts.…”
Section: Introductionmentioning
confidence: 95%
“…ii. If trait disinhibition primarily reflects overresponsiveness to threat (Blair et al, 2014) as related to impaired preparatory processing (Iacono et al, 1999) (Bechara et al, 2000;Davidson et al, 2000), and research has shown that electrodermal and fMRI responses covary (Critchley et al, 2000) and that this covariation occurs in differing task contexts, including resting state measurement (Patterson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The MTFS sample was identified from birth records from the US state of Minnesota and is broadly representative of families with twins born in that state. A complete description of the recruitment of the MTFS sample as well as evidence of sample representativeness is given in Iacono et al (1999). The MTFS samples have been followed longitudinally every 3-4 years, with in-person follow-up assessments timed to coincide with major life transitions in the life of American adolescents and young adults (Figure 1).…”
Section: Samplementioning
confidence: 99%
“…Diagnoses and symptom counts according to DSM-III-R, the diagnostic standard current at the time the MTFS was started, are generated by computer algorithm. The reliability of this consensus process for the diagnoses we assess is uniformly high (Iacono et al, 1999). …”
mentioning
confidence: 95%